Kant and the Spirit of Critique - Sallis, John, 1938- (Book collections on Project MUSE., 2020)
"This volume of the collected writings of John Sallis presents his lecture courses on Immanuel Kant. Each course takes up one of Kant's three Critiques, and thus the text as a whole treats the entirety of the Kantian critical project. Sallis displays here, as he does in all of his lecture courses, an uncanny ability to open up dense philosophical texts. Sallis patiently and successfully lays out the issues-theoretical, practical, aesthetic, and philosophical-and his critical approach to them. For students and seasoned scholars who require a step-by-step interpretation of Kant, these texts by Sallis are attuned to the spirit, structure, and principle of these foundational works."--